ANALISIS KEMAMPUAN PENYELESAIAN SOAL MODUS MEDIAN DAN MEAN MAHASISWA PENDIDIKAN MATEMATIKA PADA MATA KULIAH STATISTIK DI UNIVERSITAS MUHAMMADIYAH SORONG - Mahendra, Faisal Eka; Irna Rusani; Andi Maryam; Andini, Rya; Nova Yuliani (Qalam : Jurnal Ilmu Kependidikan, 2024)
This study aims to identify the types and factors of errors made by students in the Mathematics Education Program at Universitas Muhammadiyah Sorong when solving problems related to mode, median, and mean, which are part of statistical methods material. This research employs a qualitative descriptive approach, involving six students from the Mathematics Education program who made the most errors. Data were collected through written tests completed by these six subjects. The data analysis technique involved examining answer sheets, scoring each question, presenting the percentage data for each type of error, and drawing conclusions. Based on the entire analysis, it was found that the types of errors in calculations were 22%, errors in the use of formulas were 28%, and errors in determining the total frequency were 6%. The factors contributing to these errors include a lack of accuracy in calculations and difficulty in finding the correct formulas. The conclusion of this study is that students frequently make errors in solving mode, median, and mean problems, particularly in understanding the material, using formulas, and producing the final answer